Safety and immunogenicity of a Vi-DT typhoid conjugate vaccine: Phase I trial in Healthy Filipino adults and children. Issue 26 (18th June 2018) - Capeding, Maria Rosario; Teshome, Samuel; Saluja, Tarun; Syed, Khalid Ali; Kim, Deok Ryun; Park, Ju Yeon; Yang, Jae Seung; Kim, Yang Hee; Park, Jiwook; Jo, Sue-Kyoung; Chon, Yun; Kothari, Sudeep; et al.
Highlights: Vi-DT is safe and well tolerated in participants aged 2–45 years. Significantly higher immune responses post Vi-DT compared to Vi polysaccharide vaccine. No further increase in GMT post second dose as compared to post first dose of Vi-DT. Abstract: Background: Typhoid fever remains a major public health problem in low- and middle-income countries where children aged 2–14 years bear the greatest burden. Vi polysaccharide is poorly immunogenic in children <2 years of age, and protection in adults is modest. The limitations of Vi polysaccharide vaccines can be overcome by conjugation of the Vi to a carrier protein. A typhoid conjugate vaccine composed of Vi polysaccharide conjugated to diphtheria toxoid (Vi-DT) has been developed. The Phase I study results are presented here. Methods: This was a randomized, observer-blinded Phase I study to assess the safety and immunogenicity of Vi-DT compared to Vi polysaccharide vaccine, conducted in Manila, Philippines. Participants enrolled in an age de-escalation manner (18–45, 6–17 and 2–5 years) were randomized between Test (Vi-DT, 25 µg) administered at 0 and 4 weeks and Comparator (Vi polysaccharide, Typhim Vi® and Vaxigrip®, Sanofi Pasteur) vaccines. Results: A total of 144 participants were enrolled (48 by age strata, 24 in Test and Comparator groups each). No serious adverse event was reported in either group. Solicited and unsolicited adverse events were mild or moderate in both groups with the exception of a 4-year old girl in Test group with grade 3 fever which resolved without sequelae. All participants in Test group seroconverted after first and second doses of Vi-DT while the proportions in the Comparator group were 97.1% and 97.2%, after first dose of Typhim Vi® and second dose of Vaxigrip®, respectively. Vi-DT showed 4-fold higher Geometric Mean Titers (GMT) compared to Typhim Vi® (adjusted for age strata, p < 0.001). No further increase of GMT was detected after the second dose of Vi-DT. Anti-DT IgG seroresponse rates were 81.2% and 84.5% post first and second Vi-DT doses, respectively. Conclusions: Vi-DT vaccine was safe, well-tolerated and immunogenic in participants aged 2–45 years. ClinicalTrials.gov registration number: NCT02645032.